2010
DOI: 10.4049/jimmunol.0903516
|View full text |Cite
|
Sign up to set email alerts
|

Interdisciplinary Analysis of HIV-Specific CD8+ T Cell Responses against Variant Epitopes Reveals Restricted TCR Promiscuity

Abstract: HIV-1–specific CTL responses play a key role in limiting viral replication. CTL responses are sensitive to viral escape mutations, which influence recognition of the virus. Although CTLs have been shown to recognize epitope variants, the extent of this cross-reactivity has not been quantitatively investigated in a genetically diverse cohort of HIV-1–infected patients. Using a novel bioinformatic binding prediction method, we aimed to explain the pattern of epitope-specific CTL responses based on the patients’ … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
31
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 35 publications
(36 citation statements)
references
References 46 publications
4
31
1
Order By: Relevance
“…MHC I-restricted epitope escape has been shown to dramatically reduce the magnitude of the CD8 + T cell response (49). Previous studies have also found associations between higher magnitude of T cell responses and rapid escape (43, 50).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MHC I-restricted epitope escape has been shown to dramatically reduce the magnitude of the CD8 + T cell response (49). Previous studies have also found associations between higher magnitude of T cell responses and rapid escape (43, 50).…”
Section: Discussionmentioning
confidence: 99%
“…Epitope mutations that evade these immune responses can become fixed in the viral population as a result of the selective pressure from HIV-specific CD8 + T cells (15). Viral mutations can have an impact on peptide-MHC class I–T cell receptor (TCR) interactions (6, 7), binding of the peptide to the MHC class I molecules (5, 810), and the intracellular processing of the viral peptides (1113). Several mutations completely abrogate an epitope-specific CD8+ T cell response while others are cross-recognized by the TCR of available T cell clones or induce recruitment of newly developed T cell clonotypes (14).…”
Section: Introductionmentioning
confidence: 99%
“…It is important to consider that epitope variant recognition has been widely reported in the context of progressive infection (28)(29)(30)(31). To date, variant recognition assessments have often focused on a limited number of epitopes and/or epitope variants, largely due to limited sample availability and the prohibitive cost of generating proteome-wide variant peptide sets.…”
mentioning
confidence: 99%
“…Despite this variability, five epitope positions (p4-p8 -gates 1-3) and four MHC-I residues were consistently indicated as involved with TCR interactions, being present in more than 85% of these complexes. The P4-P6 positions of the epitope had already been observed as being directly involved in the stimulation of immunogenicity (Calis et al, 2012(Calis et al, , 2013Frankild et al, 2008;Hoof et al, 2010;Rudolph et al, 2006;Wucherpfennig et al, 2009). Several residues over the pMHC-I surface might participate in the interaction with the TCR, influencing the specific level of T-cell stimulation that will be triggered by each pMHC-I.…”
Section: Resultsmentioning
confidence: 99%